Clinical Supervision in the Addictions Field: A Case Example of Effective Gatekeeping. Issue 1 (2nd January 2016) - Fulton, Cheryl L.; Kjellstrand Hartwig, Elizabeth; Ybañez-Llorente, Kathy; Schmidt, Eric
ABSTRACT: Clinical supervision is essential to the development of competent, ethical, and professional practice among substance abuse counselors. A vital role of supervisors is to act as gatekeepers responsible for protecting clients and the profession. Many supervisors in the addictions field lack formal education and training in supervision and, hence, could benefit from information and guidance in performing challenging supervisory tasks such as gatekeeping. This article focuses on the key elements of effective supervision, particularly with regard to supervisee assessment, remediation, and dismissal, all while considering the common pitfalls experience and encountered by those receiving supervision. These processes are presented and illustrated through a case example as a means of providing practical guidance to those who supervise current and aspiring substance abuse counselors.